The Impact of 2008 Global Financial Crisis on the Performance of Selected Indonesian Stocks: A Preliminary Study - Suparman, Edwin (UI Scholars Hub, 2012)
This research is a preliminary study that analyzes the impact of the US ﬁnancial markets on Indonesian ﬁnancial markets during the 2008 global ﬁnancial crisis. It speciﬁcally investigates the occurrence of contagion effect in the Indonesian IHSG index and selected LQ45 stocks with the US S&P500 index by the measurement of correlation using simple correlation, EWMA, OGARCH, and DCC GARCH. It also attempts to discuss on the decoupling of Indonesian market and provide recommendations on dealing with future similar events.